1981
DOI: 10.1210/endo-108-4-1353
|View full text |Cite
|
Sign up to set email alerts
|

Geometric Isomers of Substituted Triphenylethylenes and Antiestrogen Action

Abstract: The estrogenic and antiestrogenic activities of tamoxifen ICI 47,699, enclomiphene, zuclomiphene, and the geometric isomers of monohydroxytamoxifen and CI628 were determined in the 3-day immature rat uterine weight test. Tamoxifen, enclomiphene, and the releated geometric isomers of monohydroxytamoxifen and CI628 were partially estrogenic with antiestrogenic properties. ICI 47,699 and zuclomiphene were predominantly estrogenic; however, an antiestrogen effect for zuclomiphene (100 micrograms daily) was demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(31 citation statements)
references
References 28 publications
2
29
0
Order By: Relevance
“…Previous studies examining the antiestrogenic properties of TAM metabolite isomers have been hindered by the interconversion between the cis-and trans-isomers of TAM and TAM metabolites shown to occur in previous experimental systems (Jordan et al, 1981;Lieberman et al, 1983;Katzenellenbogen et al, 1984). The present study is the first to examine the antiestrogenic properties of relatively pure isomers of both 4-OH-TAM and endoxifen.…”
Section: Antiestrogenic Activity Of Tamoxifen Metabolitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies examining the antiestrogenic properties of TAM metabolite isomers have been hindered by the interconversion between the cis-and trans-isomers of TAM and TAM metabolites shown to occur in previous experimental systems (Jordan et al, 1981;Lieberman et al, 1983;Katzenellenbogen et al, 1984). The present study is the first to examine the antiestrogenic properties of relatively pure isomers of both 4-OH-TAM and endoxifen.…”
Section: Antiestrogenic Activity Of Tamoxifen Metabolitesmentioning
confidence: 99%
“…Interpretation of results from previous studies was difficult because of the possible interconversion between isomers. It was originally suggested that because cis-TAM is estrogenic, the antiestrogenic properties of cis-4-OH-TAM in a rat uterine weight test model may be due to interconversion to its trans-form (Jordan et al, 1981). A later study using a prolactin synthesis model demonstrated a stronger antiestrogenic effect for trans-4-OH-TAM compared with cis-4-OH-TAM and that neither isomer exhibited estrogenic properties, but these data were also confounded by the possibility of interconversion between isomers (Lieberman et al, 1983).…”
Section: Antiestrogenic Activity Of Tamoxifen Metabolitesmentioning
confidence: 99%
“…The principle is exemplified by the cis and trans geometric isomers of tamoxifen or clomiphene. Tamoxifen and enclomiphene (the trans isomers) are both paitial estrogen agonists in the immature rat with antiestrogenic properties (93)(94)(95). In contrast, the cis isomers, ICI 47,699 (Fig.…”
Section: Structure-activity Studies In Vivo: Correlation With Estrogementioning
confidence: 99%
“…In contrast, the cis isomers, ICI 47,699 (Fig. 15) and zuclomiphene, are both estrogens (93)(94)(95). These types of observations have been used to develop models to describe estrogen and antiestrogen action in the rat (94,96).…”
Section: Structure-activity Studies In Vivo: Correlation With Estrogementioning
confidence: 99%
See 1 more Smart Citation